Пространственные задачи термовязкопластичности: фокус на украинские исследования (обзор) - Шевченко, Ю.Н.; Савченко, В.Г. (Прикладная механика, 2016)
Наведено методи і результати дослідження тривимірного в’язкопластичного напружено-деформованого стану елементів машинобудівних конструкцій при термосиловому навантаженні. Розглянуто наступні класи задач термов’язкопластичності: осесиметричні задачі; неосесиметричні задачі для тіл обертання; тривимірні задачі для тіл довільної форми; тривимірні задачі для ізотропних та анізотропних тіл обертання. The methods and results of studying the three-dimensional viscoplastic stress-strain state of engineering constructions under thermal force loading are presented. The following classes of thermoviscoelasticity problems are considered: axisymmetric problems; nonaxisymmetric problems for bodied of revolution; three-dimensional problems for bodies of arbitrary shape; three-dimensional problems for isotropic and anisotropic bodies of revolution.